Contributions of virtual manipulative materials to mathematics teaching: an integrative literature review - Michelsch João da Silva; Carla Denize Ott Felcher; Vanderlei Folmer (Amazônia, 2023)
The research aims to verify the potential of using virtual manipulative materials to teach mathematics in Basic Education. With a qualitative approach, this integrative review presents an analysis of fourteen articles written in English, Spanish and Portuguese. The database selected to define the sample was the CAPES journal portal. The study is guided by the following question: what are the possible contributions of using virtual manipulative materials to the process of teaching and learning mathematics in Basic Education? Among the potentials raised, the development of skills and competencies for living in the 21st century, creativity, strengthening motivation, creating autonomy, self-reflection and self-criticism and better understanding of the content stand out. In the end, it suggests that new research be carried out in the area, especially from the perspective of teacher training to qualify them to use technological tools in the classroom.